High-toughness and high-strength rubber composite material and preparation method thereof

By using bisimidazole aprotic ionic liquid containing bisimidazole in rubber composites, the problems of long vulcanization time, poor toughness and stability need to be improved in the existing rubber/silane coupling agent system are solved, and the preparation of high-toughness and high-strength rubber composites is achieved, which significantly improves the mechanical properties and stability of the material.

CN119798813AActive Publication Date: 2025-04-11XIAMEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510113541.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-11
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing rubber/silane black/silane coupling agent systems have problems such as long vulcanization time, poor toughness and stability that need to be improved, making it difficult to meet the needs of high-toughness and high-strength rubber composite materials.

Method used

Bisimidazole aprotic ionic liquid containing bisimidazole is combined with rubber, white carbon black, silane coupling agent, stearic acid, zinc oxide, vulcanizing agent, promoter and paraffin. Through mechanisms such as click chemical reactions and ionic bond formation, the cross-linking density and toughness of rubber composite materials are improved and the vulcanization time is shortened.

Benefits of technology

It significantly improves the mechanical strength and toughness of rubber composite materials, shortens vulcanization time, improves the dispersion and compatibility of white carbon black in rubber matrix, thereby improving the stability of the material and industrial production potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798813A_ABST
    Figure CN119798813A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness and high-strength rubber composite material and a preparation method thereof. The high-toughness and high-strength rubber composite material is prepared by uniformly mixing a rubber matrix, a bis-thiol-containing bis-imidazole aprotic ionic liquid, white carbon black, a silane coupling agent, stearic acid, zinc oxide, a vulcanizing agent, an accelerant and paraffin and then carrying out hot-pressing vulcanization. The bis-thiol-containing bis-imidazole aprotic ionic liquid is grafted on a rubber side chain through a click chemical reaction, so that the crosslinking density of the rubber composite material is improved; under the action of external force, the toughness of the rubber composite material can be improved; in the rubber vulcanization forming process, the vulcanization time can be shortened, and mutual use of organic-inorganic interfaces is improved; in addition, the dispersion of the white carbon black in a rubber matrix can be improved; the prepared high-toughness and high-strength rubber composite material has excellent mechanical property and fatigue resistance, is wide in application range and can be industrially produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber composite materials, and particularly relates to a high-toughness and high-strength rubber composite material and a preparation method thereof. Background Art

[0002] Since the discovery in 1893 that sulfur can vulcanize and cross-link rubber to form a stable material, vulcanized rubber has been widely used in production and life, such as rubber tires, seals, damping systems, soft robots, wearable electronic devices and flexible sensors. However, although the three-dimensional network system formed by vulcanized rubber has improved the mechanical strength of rubber to a certain extent, it still cannot meet the use requirements of most engineering rubber products, and excessive vulcanization will also lead to a significant decrease in rubber toughness. Therefore, industry usually enhances rubber performance by compounding nanofillers such as carbon black, white carbon black, and clay with rubber.

[0003] Silica is a type of inorganic nanomaterial with excellent rigidity, stability and flame retardancy. Filling in rubber materials can significantly enhance their mechanical properties, thermal stability and acid and alkali corrosion resistance. Usually, silica is compounded with silane coupling agents to improve its dispersion compatibility in rubber, thereby improving the mechanical properties of rubber products. This has been reflected in a large number of reports and has also generated great application value in production practice. However, with the rapid development of modern industry, higher requirements have been placed on the performance of rubber composite materials. For the rubber / silica / silane coupling agent system, there are currently three issues that need to be optimized and improved:

[0004] 1. Long vulcanization time: Long-term high-temperature vulcanization not only consumes a lot of energy resources, but also may cause oxidative degradation or structural reaction, causing the rubber to reduce strength or lose elasticity;

[0005] 2. Poor toughness: Toughness and strength are usually contradictory in materials. Although the introduction of rigid inorganic nanoparticles can significantly enhance the mechanical strength of rubber composites, it will sacrifice the excellent elasticity of rubber itself;

[0006] 3. Stability needs to be improved: Although the combination of white carbon black and silane coupling agent significantly improves the mechanical properties of rubber composites, under long-term external force, the mechanical properties and stability of rubber composites mainly depend on the magnitude of the rubber-filler interface interaction force.

[0007] Therefore, in order to optimize the problems existing in the existing rubber / silica / silane coupling agent system and further improve the mechanical properties and stability of rubber composites, it is urgently necessary to develop high-toughness and high-strength rubber composites. Summary of the invention

[0008] The purpose of the present invention is to overcome the defects of the prior art and provide a high-toughness and high-strength rubber composite material.

[0009] Another object of the present invention is to provide a method for preparing the above-mentioned high-toughness and high-strength rubber composite material.

[0010] The technical solution of the present invention is as follows:

[0011] A high-toughness and high-strength rubber composite material is prepared by uniformly mixing a rubber matrix, a diimidazole aprotic ionic liquid containing a dithiol group, white carbon black, a silane coupling agent, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin wax, and then hot-pressing vulcanization, wherein the structural formula of the diimidazole aprotic ionic liquid containing a dithiol group is:

[0012]

[0013] Wherein, R1 is selected from sulfonate anion moieties and carboxylate anion moieties, and the structures are respectively n=1-11,

[0014] R2 is a C1-12 aliphatic alkane chain or alkoxy chain,

[0015] R3 is a C1-12 aliphatic alkane chain or an alkoxy chain.

[0016] In a preferred embodiment of the present invention, the rubber matrix is ​​selected from natural rubber, styrene-butadiene rubber, epoxy rubber and silicone rubber.

[0017] In a preferred embodiment of the present invention, the preparation method of the dithiol-containing bisimidazolyl aprotic ionic liquid comprises the following steps:

[0018] a. Alkylation reaction, the reaction route is

[0019]

[0020] b. Two-step anion exchange reaction, the reaction route is:

[0021]

[0022] In a preferred embodiment of the present invention, the silane coupling agent is selected from mercapto-based silane coupling agents and vinyl-based silane coupling agents.

[0023] In a preferred embodiment of the present invention, the silane coupling agent is bis-[γ-(triethoxysilyl)propyl]tetrasulfide.

[0024] In a preferred embodiment of the present invention, the vulcanizing agent is sulfur.

[0025] In a preferred embodiment of the present invention, the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide.

[0026] In a preferred embodiment of the present invention, the rubber substrate is natural rubber or styrene-butadiene rubber, the silane coupling agent is bis-[γ-(triethoxysilyl)propyl] tetrasulfide, the vulcanizing agent is sulfur, the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide, and the structural formula of the dithiol-containing bisimidazolyl aprotic ionic liquid is

[0027]

[0028] In a preferred embodiment of the present invention, the mass ratio of the rubber matrix, the dithiol-containing bisimidazolyl aprotic ionic liquid, white carbon black, silane coupling agent, stearic acid, zinc oxide, vulcanizing agent, accelerator and paraffin is 60-100:1-20:10-80:1-20:1-3:2-4:1-4:1-3:1-3.

[0029] The preparation method of the high-toughness and high-strength rubber composite material comprises: kneading the rubber matrix, the disimidazole non-protonic ionic liquid containing a dithiol group, white carbon black, a silane coupling agent, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin in an internal mixer for 7-9 minutes, then discharging the rubber prepolymer through an open mixer, determining the positive vulcanization time to be 5-20 minutes through a rotorless vulcanizer, and hot pressing the rubber composite material with high toughness and high strength through a flat hot press at a pressure of 14-16 MPa and 145-155° C. for 5-20 minutes.

[0030] The beneficial effects of the present invention are:

[0031] 1. The bisimidazolyl non-proton ionic liquid containing a dithiol group in the present invention can undergo a thiol-double bond click chemical reaction with the unsaturated double bonds in the rubber. Since one ionic liquid molecule contains two thiol groups, different rubber molecular chains can be covalently cross-linked, thereby increasing the cross-linking density of the rubber composite material and further improving its mechanical strength.

[0032] 2. Ionic bonds are formed between anions and cations in the dithiol-containing bisimidazolate non-proton ionic liquid of the present invention. The ionic bonds have the characteristics of strong force and no directionality. Under the action of external force, the ionic bonds can dynamically and efficiently dissociate and associate, produce an energy dissipation effect, and thus improve the toughness of the rubber composite material.

[0033] 3. The dithiol-containing bisimidazolyl non-protonic ionic liquid of the present invention can catalyze the silanization reaction between the silane coupling agent and white carbon black under high temperature conditions, effectively shortening the vulcanization time, and at the same time improving the problem of easy agglomeration of white carbon black in the rubber matrix due to thermodynamic incompatibility, achieving nanoscale uniform dispersion of white carbon black in the rubber matrix, significantly enhancing the interaction at the interface of organic-inorganic components, and thus improving the mechanical strength and stability of the rubber composite material during use.

[0034] 4. The dithiol-containing bisimidazolyl non-protonic ionic liquid of the present invention is fixed on the rubber side chain by covalent grafting, and has excellent stability and durability, effectively avoiding the occurrence of the phenomenon of ionic liquid migration or volatilization from the rubber under conditions of high temperature, liquid environment, low pressure, etc.

[0035] 5. The presence of hydrogen bonds and ion-dipole interactions between the dithiol-containing bisimidazolate aprotic ionic liquid and silica in the present invention can further improve the dispersibility and compatibility of silica in the rubber matrix, thereby enabling the rubber composite material to obtain excellent mechanical properties.

[0036] 5. The rubber composite material of the present invention has obvious modification effect, simple preparation process, mild preparation conditions, low cost and good industrial production potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the ionic liquid Br-IL in Example 1 of the present invention 1 H NMR spectrum.

[0038] Figure 2 The diimidazole aprotic ionic liquid containing dithiol groups in Example 1 of the present invention 1 H NMR spectrum.

[0039] Figure 3 This is an optical photograph of the high-toughness and high-strength rubber composite material in Example 1 of the present invention.

[0040] Figure 4 is the ionic liquid Br-IL in Example 2 of the present invention 1 H NMR spectrum.

[0041] Figure 5 The diimidazole aprotic ionic liquid containing dithiol groups in Example 2 of the present invention 1 H NMR spectrum.

[0042] Figure 6 The cross-sectional SEM photos of the high-toughness and high-strength rubber composite material in Example 1 of the present invention and the comparative rubber composite material in Comparative Example 1 are shown. DETAILED DESCRIPTION

[0043] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.

[0044] Example 1

[0045] a. Alkylation reaction:

[0046] Ethyl bromide (1.43 g, 13.2 mmol) and diimidazole butane (1 g, 5.3 mmol) were dissolved in 15 mL of acetonitrile, stirred at 80 ° C for 24 h under a nitrogen atmosphere, and the solvent was removed by a rotary evaporator. 10 mL of anhydrous ether was added for shaking and washing. After filtering and drying, the intermediate product ionic liquid Br-IL was obtained. Its structural formula is as follows:

[0047]

[0048] Its physical property characterization data are: 1 H NMR (500MHz, DMSO-d6) δ = 9.34 (d, J = 1.7 Hz, 2H, CH), 7.84 (dt, J = 6.4, 1.9 Hz, 4H, CH), 4.28–4.18 (m, 8H, CH2), 1.81 (quint, J = 3.3 Hz, 4H, CH2), 1.43 (t, J = 7.3 Hz, 6H, CH3). It can be seen that the product is an ionic liquid Br-IL; 1 H NMR spectrum Figure 1 As shown;

[0049] b. Two-step anion exchange reaction:

[0050] The Br-IL (1 g, 2.5 mmol) prepared in step a was dissolved in 5 mL of ethanol, potassium hydroxide (0.28 g, 5 mmol) was weighed and dissolved in 300 μL of deionized water, and a large amount of white precipitate KBr was produced after mixing the two, and the filtrate was filtered and collected to obtain the intermediate product ionic liquid OH-IL. 3-Mercaptopropionic acid (0.52 g, 5 mmol) was dissolved in 1 mL of ethanol and slowly added dropwise to OH-IL. After shaking for 1 min, the ethanol was removed by a rotary evaporator, and the water was removed by freeze drying for 12 h to obtain the target product, a bisimidazolyl aprotic ionic liquid containing a dithiol group, and its structural formula is as follows:

[0051]

[0052] Its characterization data are: 1H NMR (500MHz, DMSO-d6) δ = 9.66 (s, 2H, CH), 7.83 (dt, J = 6.8, 1.9 Hz, 4H, CH), 4.26 (t, J = 6.2 Hz, 4H, CH2), 4.21 (q, J = 7.3 Hz, 4H, CH2), 2.53 (t, J = 7.0 Hz, 4H, CH2), 2.20 (t, J = 7.0 Hz, 4H, CH2), 1.80 (quint, J = 6.4 Hz, 4H, CH2), 1.43 (t, J = 7.3 Hz, 6H, CH3). It can be seen that the product is a bisimidazolyl aprotic ionic liquid containing a dithiol group; 1 H NMR spectrum Figure 2 shown.

[0053] According to weight, 100 parts of natural rubber, 6 parts of the above-mentioned dithiol-containing bisimidazolyl aprotic ionic liquid, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl] tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide and 1 part of paraffin were mixed in an internal mixer for 8 minutes, and then the rubber prepolymer was obtained by sheeting through an open mixer. The positive vulcanization time was determined to be 9.3 minutes by a rotorless vulcanizer, and the prepolymer was obtained by hot pressing at a pressure of 15MPa and 150°C for 9.3 minutes on a flat hot press. Figure 3 The high toughness and high strength rubber composite material shown.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that the chemical structural formula of the prepared bisimidazolyl aprotic ionic liquid containing bisthiol groups is different. The specifics of this embodiment are as follows:

[0056] a. Alkylation reaction:

[0057] 1-Bromododecane (3.27 g, 13.1 mmol) and bisimidazole butane (1 g, 5.3 mmol) were dissolved in 15 mL of acetonitrile, stirred at 80 ° C for 24 h under nitrogen atmosphere, and the solvent was removed by rotary evaporator, and then 10 mL of anhydrous ether was added for shaking and washing. After filtering and drying, the intermediate product ionic liquid Br-IL was obtained, and its structural formula is as follows:

[0058]

[0059] Its physical property characterization data are: 1H NMR (500MHz, DMSO-d6) δ = 9.38 (d, J = 1.7 Hz, 2H, CH), 7.85 (dt, J = 7.4, 2.0 Hz, 4H, CH), 4.26 (d, J = 6.2 Hz, 4H, CH2), 4.18 (t, J = 7.2 Hz, 4H, CH2), 1.80 (m, 8H, CH2), 1.24 (s, 36H, CH2), 0.86 (t, J = 6.8 Hz, 6H, CH3). It can be seen that the product is an ionic liquid Br-IL; 1 HNMR spectrum Figure 4 As shown;

[0060] b. Two-step anion exchange reaction:

[0061] The Br-IL (1 g, 1.45 mmol) prepared in step a was dissolved in 5 mL of ethanol, potassium hydroxide (0.16 g, 2.9 mmol) was weighed and dissolved in 150 μL of deionized water, and a large amount of white precipitate KBr was produced after mixing the two, and the filtrate was filtered and collected to obtain the intermediate product ionic liquid OH-IL. 3-Mercaptopropionic acid (0.31 g, 2.9 mmol) was dissolved in 1 mL of ethanol and slowly added dropwise to OH-IL. After shaking for 1 min, the ethanol was removed by a rotary evaporator, and the water was removed by freeze drying for 12 h to obtain the target product, a bisimidazolyl aprotic ionic liquid containing a dithiol group, and its structural formula is as follows:

[0062]

[0063] Its characterization data are: 1 H NMR (500MHz, DMSO-d6) δ = 9.80 (s, 2H, CH), 7.84 (dt, J = 21.7, 1.8Hz, 4H, CH), 4.28 (d, J = 6.4Hz, 4H, CH2), 4.17 (t, J = 7.2Hz, 4H, CH2), 2.55 (t, J = 7.0Hz, 4H, CH2), 2.26 (t, J = 7.0Hz, 4H, CH2), 1.80 (m, 8H, CH2), 1.23 (s, 36H, CH2), 0.85 (t, J = 6.9Hz, 6H, CH3). It can be seen that the product is a bisimidazolyl aprotic ionic liquid containing a dithiol group; 1 H NMR spectrum Figure 5 shown.

[0064] The invention discloses a method for preparing a rubber prepolymer comprising the following steps: mixing 100 parts of natural rubber, 6 parts of a diimidazole non-protonic ionic liquid containing a dithiol group, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl] tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide and 1 part of paraffin in an internal mixer for 8 minutes, and then discharging the mixture into sheets through an open mixer.

[0065] The remaining steps are the same as those in Example 1 to obtain the high-toughness and high-strength rubber composite material.

[0066] Example 3

[0067] The difference between this embodiment and embodiment 1 is that the chemical structural formula of the obtained bisimidazolyl aprotic ionic liquid containing bisthiol groups is different, and the alkylation reaction in step a is exactly the same. The details of this embodiment are as follows:

[0068] Br-IL (1 g, 2.5 mmol) prepared in step a was dissolved in 5 mL of ethanol; sodium 3-mercapto-1-propanesulfonate (0.90 g, 5 mmol) was dissolved in 300 μL of deionized water and slowly added dropwise to Br-IL. After shaking for 1 min, the two were mixed to produce a large amount of white precipitate NaBr. The filtrate was filtered and collected, and the ethanol was removed by a rotary evaporator. The water was removed by freeze drying for 12 h to obtain the target product, a dithiol-containing bisimidazolyl aprotic ionic liquid, whose structural formula is as follows:

[0069]

[0070] The invention discloses a method for preparing a rubber prepolymer comprising the following steps: mixing 100 parts of natural rubber, 6 parts of a diimidazole non-protonic ionic liquid containing a dithiol group, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl] tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide and 1 part of paraffin in an internal mixer for 8 minutes, and then discharging the mixture into sheets through an open mixer.

[0071] The remaining steps are the same as those in Example 1 to obtain the high-toughness and high-strength rubber composite material.

[0072] Example 4

[0073] The difference between this embodiment and embodiment 1 is that natural rubber is replaced by styrene-butadiene rubber. By weight, 100 parts of styrene-butadiene rubber, 6 parts of diimidazole aprotic ionic liquid containing dithiol groups, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfenamide and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted through an open mixer to obtain a rubber prepolymer.

[0074] The remaining steps are the same as those in Example 1 to obtain the high-toughness and high-strength rubber composite material.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that no diimidazole non-protonic ionic liquid containing a dithiol group is added. By weight, 100 parts of natural rubber, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfenamide and 1 part of paraffin are mixed in an internal mixer for 8 minutes and then sheeted through an open mixer to obtain a rubber prepolymer.

[0077] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 1 is that the ionic liquid is a biimidazole non-protonic ionic liquid with an amino group. Specifically, Br-IL (1g, 1.45mmol) was dissolved in 5mL of ethanol, potassium hydroxide (0.16g, 2.9mmol) was weighed and dissolved in 150μL of deionized water, and a large amount of white precipitate KBr was produced after mixing the two. The filtrate was filtered and collected to obtain the intermediate product ionic liquid OH-IL. 3-aminopropionic acid (0.26g, 2.9mmol) was dissolved in 1mL of ethanol and slowly added dropwise to OH-IL. After shaking the reaction for 1min, the ethanol was removed by a rotary evaporator, and the water was removed by freeze drying for 12h to obtain the target product, a biimidazole non-protonic ionic liquid with an amino group, and its structural formula is as follows:

[0080]

[0081] The invention discloses a rubber prepolymer comprising 100 parts by weight of natural rubber, 6 parts of diimidazole non-protonic ionic liquid containing a diamine group, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl] tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide and 1 part of paraffin, which are kneaded in an internal mixer for 8 minutes and then discharged through an open mixer to obtain a rubber prepolymer.

[0082] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 1 is that the ionic liquid is a monoimidazole aprotic ionic liquid with a thiol group. Specifically, 1-butyl-3-methylimidazolium bromide (1 g, 4.6 mmol) was dissolved in 5 mL of ethanol, potassium hydroxide (0.26 g, 4.6 mmol) was weighed and dissolved in 300 μL of deionized water, and a large amount of white precipitate KBr was produced after the two were mixed. The filtrate was filtered and collected, 3-mercaptopropionic acid (0.49 g, 4.6 mmol) was dissolved in 1 mL of ethanol, and slowly added dropwise to the filtrate. After shaking the reaction for 1 min, the ethanol was removed by a rotary evaporator, and the water was removed by freeze drying for 12 h to obtain the target product, a monoimidazole aprotic ionic liquid with a thiol group, and its structural formula is as follows:

[0085]

[0086] The invention discloses a rubber prepolymer comprising 100 parts by weight of natural rubber, 6 parts of a mercapto-containing monoimidazole non-protonic ionic liquid, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide and 1 part of paraffin, which are kneaded in an internal mixer for 8 minutes and then discharged through an open mixer to obtain a rubber prepolymer.

[0087] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.

[0088] Comparative Example 4

[0089] The difference between this comparative example and Example 1 is that the ionic liquid is a bisimidazolyl proton ionic liquid with a thiol group. Specifically, 3-mercaptopropionic acid (1 g, 9.4 mmol) and bisimidazolyl butane (0.9 g, 4.7 mmol) were dissolved in 5 mL of ethanol, stirred at room temperature for 4 h under a nitrogen atmosphere, and the solvent was removed by a rotary evaporator to obtain the target product, a bisimidazolyl proton ionic liquid with a thiol group, whose structural formula is as follows:

[0090]

[0091] The invention discloses a method for preparing a rubber prepolymer. The method comprises the following steps: mixing 100 parts of natural rubber, 6 parts of bisimidazolyl proton ionic liquid with mercapto group, 60 parts of white carbon black, 6 parts of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, 2 parts of stearic acid, 3 parts of zinc oxide, 2.5 parts of sulfur, 1 part of N-cyclohexyl-2-benzothiazole sulfonamide and 1 part of paraffin in an internal mixer for 8 minutes, and then discharging the mixture into sheets through an open mixer.

[0092] The remaining steps were the same as those in Example 1 to prepare a comparative rubber composite material.

[0093] Example 4

[0094] The following performance tests were performed on Examples 1 to 4 of the present invention and Comparative Examples 1 to 4, and the test items and methods are as follows:

[0095] Structural characterization of ionic liquids: The synthesized ionic liquids were characterized by AVANCE III HD 500MHZ NMR. 1 For H NMR characterization, 5 mg of the sample was dissolved in 600 μL of DMSO-d6 and the number of scans was set to 16.

[0096] Determination of vulcanization curve: The vulcanization curve of the rubber composite prepared above was tested using a BL-6190 rotorless vulcanizer (Baisheng Machinery Equipment Factory). According to GB / T 9869-2014 standard, the temperature was set at 150°C and the duration was set at 30 min. The vulcanization curve of the mixed rubber was measured and the positive vulcanization time T was determined. 90 .

[0097] Stress-strain property test: According to the method specified in GB / T 528-2009, the 100% modulus stress, 300% modulus stress, tensile strength and elongation at break of the rubber composite material prepared as above were measured.

[0098] Toughness of rubber: The area of ​​the closed curve between the stress-strain curve and the X-axis in the stress-strain performance test of the sample.

[0099] Rubber crosslink density: The crosslink density of vulcanized rubber was determined by the equilibrium swelling method. Specifically, 1 g of vulcanized rubber was immersed in 30 mL of toluene for three days, with the toluene replaced every 24 hours. After the immersion, the solvent on the surface of the sample was quickly absorbed with a paper towel, and the sample weight at this time (m1) was weighed. Then, the sample was vacuum dried in a vacuum oven at 60°C to constant weight, and the sample weight at this time (m2) was recorded. The crosslink density V of the sample c Calculated according to the Flory-Rehner equation:

[0100]

[0101] Where M c is the molecular weight between cross-linking points, calculated by the following formula:

[0102]

[0103] In the formula, ρ p is the density of NR (0.912 g / cm 3 ), V s is the molar volume of toluene (106.3 cm 3 / mol), χ is the interaction parameter between NR and toluene, V r is the volume fraction of the sample after swelling, Vr Calculated by the following formula:

[0104]

[0105] In the formula, m f is the mass of filler in the sample, ρ s is the density of toluene (0.866 g / cm 3 ).

[0106] All test results are shown in Tables 1 and 2 below.

[0107] Table 1. Experimental characterization results of samples 1 to 4

[0108]

[0109] Table 2. Experimental characterization results of comparative samples 1 to 4

[0110]

[0111]

[0112] Experimental data analysis:

[0113] The cross sections of the rubber composites prepared in Example 1 and Comparative Example 1 were characterized by scanning electron microscopy (SEM). Figure 6 ). A large number of agglomerated white carbon particles appeared inside the comparative example 1, and the dispersion compatibility in the rubber was poor. The cross section of the example 1 was flat and smooth, and no agglomeration of white carbon was observed inside, which indicated that the addition of the dithiol-containing bisimidazolyl aprotic ionic liquid improved the agglomeration of white carbon in the rubber matrix due to thermodynamic incompatibility, and achieved nanoscale dispersion in the rubber matrix.

[0114] The test data of the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 are shown in Tables 1 and 2 above. From the test results, it can be seen that the 100% tensile stress of Example 1 is 3.5 MPa, the 300% tensile stress is 12.5 MPa, the tensile strength is 29.1 MPa, and the elongation at break is 540%. Compared with Comparative Example 1 in which the dithiol-containing bisimidazolyl aprotic ionic liquid is not added, its mechanical properties are greatly improved. The curing time (T 90) is 9.3min, while the vulcanization time of Comparative Example 1 is more than twice that (19.9min). This shows that the dithiol-containing bisimidazole aprotic ionic liquid can catalyze the silanization reaction between the silane coupling agent and white carbon black at high temperature, shorten the vulcanization time, improve the dispersion compatibility of white carbon black in the rubber matrix, and significantly enhance the interaction between the organic-inorganic component interface, thereby improving the mechanical properties of the rubber composite material. The rubber composite materials prepared by changing the cationic structure on the dithiol-containing bisimidazole aprotic ionic liquid (Examples 2 and 3) and changing the type of rubber (Example 4) all maintain excellent mechanical properties, indicating the universality of adding dithiol-containing bisimidazole aprotic ionic liquid in the rubber composite material system.

[0115] Compared with Example 1, the mechanical properties of the rubber composites prepared by replacing the terminal active functional groups of the dithiol-containing biimidazole aprotic ionic liquid with amino groups (Comparative Example 2) and the monoimidazole aprotic ionic liquid containing thiol groups (Comparative Example 3) were significantly reduced. The crosslinking density of the samples was tested by the equilibrium swelling method. The crosslinking density of Example 1 was 2.6×10 -4 mol / cm 3 , while Comparative Examples 2 and 3 are only 1.8×10 -4 mol / cm 3 and 2.1×10 -4 mol / cm 3 This is because the amino group cannot undergo chemical coupling reaction with the double bonds on the rubber chain. Therefore, the amino-containing bisimidazolate non-protonic ionic liquid in Comparative Example 2 can only catalyze the silanization reaction between white carbon black and Si69, and cannot further increase its chemical crosslinking density. The mercapto-containing monoimidazole non-protonic ionic liquid can only undergo click chemical reaction with the double bonds on the rubber molecular chain at one end, and cannot crosslink different rubber molecular chains. Therefore, it cannot increase its crosslinking density, resulting in limited improvement in the mechanical properties of the rubber composite material.

[0116] The toughness of Example 1 is 82.7 MJ / m 3 The toughness of comparative example 3 is 70.6MJ / m 3 This is because both ends of the diimidazole non-proton ionic liquid containing a thiol group are chemically coupled to the rubber molecular chain. Under the action of external force, the extension and movement of the rubber molecular chain will cause continuous dissociation and association between anions and cations, dissipating a large amount of energy, and thus having higher toughness. In addition, the effect of the type of ionic liquid (proton type and non-proton type) on the toughness of the rubber composite material is compared. The toughness of the rubber composite material prepared by adding the diimidazole proton ionic liquid containing a thiol group (Comparative Example 4) is 76.4MJ / m 3This indicates that the addition of dithiol-containing bisimidazolate aprotic ionic liquid can bring better toughness improvement to rubber composites. This is because the Coulomb force between anions and cations in protic ionic liquids is weaker than that in aprotic ionic liquids, so the dissipated energy is lower.

[0117] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A high-toughness and high-strength rubber composite material, characterized in that: The rubber matrix, the diimidazole non-protonic ionic liquid containing dithiol groups, white carbon black, a silane coupling agent, stearic acid, zinc oxide, a vulcanizing agent, an accelerator and paraffin are uniformly mixed and then hot-pressed and vulcanized to prepare the product. The structural formula of the diimidazole non-protonic ionic liquid containing dithiol groups is: Wherein, R1 is selected from sulfonate anion moieties and carboxylate anion moieties, and the structures are respectively n=1-11, R2 is a C1-12 aliphatic alkane chain or alkoxy chain, R3 is a C1-12 aliphatic alkane chain or an alkoxy chain.

2. A high-toughness and high-strength rubber composite material as claimed in claim 1, characterized in that: The rubber matrix is ​​selected from natural rubber, styrene-butadiene rubber, epoxy rubber and silicone rubber.

3. A high-toughness and high-strength rubber composite material as claimed in claim 1, characterized in that: The preparation method of the diimidazole aprotic ionic liquid containing dithiol comprises the following steps: a. Alkylation reaction, the reaction route is b. Two-step anion exchange reaction, the reaction route is:

4. A high-toughness and high-strength rubber composite material as claimed in claim 1, characterized in that: The silane coupling agent is selected from mercapto-based silane coupling agents and vinyl-based silane coupling agents.

5. A high-toughness and high-strength rubber composite material as claimed in claim 4, characterized in that: The silane coupling agent is bis-[γ-(triethoxysilyl)propyl]tetrasulfide.

6. The high-toughness and high-strength rubber composite material according to claim 1, characterized in that: The vulcanizing agent is sulfur.

7. The high-toughness and high-strength rubber composite material according to claim 1, characterized in that: The accelerator is N-cyclohexyl-2-benzothiazole sulfenamide.

8. The high-toughness and high-strength rubber composite material according to claim 1, characterized in that: The rubber substrate is natural rubber or styrene-butadiene rubber, the silane coupling agent is bis-[γ-(triethoxysilyl)propyl] tetrasulfide, the vulcanizing agent is sulfur, the accelerator is N-cyclohexyl-2-benzothiazole sulfenamide, and the structural formula of the dithiol-containing bisimidazolyl aprotic ionic liquid is 9. A high-toughness and high-strength rubber composite material according to any one of claims 1 to 8, characterized in that: The mass ratio of the rubber matrix, the dithiol-containing bisimidazolyl non-protonic ionic liquid, white carbon black, silane coupling agent, stearic acid, zinc oxide, vulcanizing agent, accelerator and paraffin is 60-100:1-20:10-80:1-20:1-3:2-4:1-4:1-3:1-3.

10. A method for preparing a high-toughness and high-strength rubber composite material according to any one of claims 1 to 9, characterized in that: include: The rubber matrix, the dithiocarbyl-containing bisimidazolyl non-protonic ionic liquid, white carbon black, silane coupling agent, stearic acid, zinc oxide, vulcanizing agent, accelerator and paraffin are mixed in an internal mixer for 7-9 minutes, and then the rubber prepolymer is sheeted out through an open mixer. The vulcanization time is determined to be 5-20 minutes by a rotorless vulcanizer. The high-toughness and high-strength rubber composite material is obtained by hot pressing at a pressure of 14-16 MPa and 145-155° C. for 5-20 minutes using a flat hot press.

Citation Information

Patent Citations

  • 2-thiothiazolyl or 2-thioimidazolyl terminated mercaptosilane coupling agent as well as synthesis method and application thereof

    CN111057269A

  • Rubber composite material filled with white carbon black synergistically modified by end group functionalized liquid rubber and sulfydryl silane coupling agent and preparation method of rubber composite material

    CN113652010A

  • Rubber composite, processing method, rubber products applying composite, and manufacturing method

    WO2018130194A1

  • Tire sidewall rubber composition, preparation method therefor, and tire

    WO2025001127A1